Breast cancer in young women: A retrospective study from tertiary care center of north India - Sharma, Deepti; Singh, Garima (South Asian Journal of Cancer, 2017)
Aim: Breast cancer is the most common cause of cancer in women worldwide. They have more aggressive clinical behaviour with poor outcomes in younger patients. The aim of this study was to evaluate the impact of age on prognosis of breast cancer in women above and under 40 years of age. Material and Methods: Medical record of 415 patients with invasive breast cancer were analysed from January 2011 to December 2014 in our department.The last was done in December 2015.All cases diagnosed with breast cancer stages I to IV were evaluated, and grouped on the basis of age [less than 40 and above 40 years].Baseline categorical variables were analysed using the Chi-square test or Fisher's exact test. Non categorical variable were analysed using t-test. Result: A total of 372 patients were reviewed because 42 patients defaulted. The median age at the time of diagnosis was 44.6 years (range 23 to 90 years).Metastasis to distant organs were more in women with age <40. Tumour relapse occurred in 131 cases, among which 84 cases died, 35 patients (26.31%) in less than 40 group vs.49 patients (20.50%) in above 40 groups. The estimated median OS in the two groups are 32 and 41 months respectively. Conclusion: The biological behaviour of breast cancer in younger age group has been shown to be associated with aggressive nature and has a worse clinical outcome as compared to that in older group.
Keywords: Breast cancer; metastasis; poor prognosis; young age